A Look at the Narrative Elements of Short Stories by Yousef Idris; Case Study: Sina Treaty. [In Persian] - Payman Salehi (International E-Research Foundation (Bonyan Pouya Pajooh Andisheh Institute), 2018)
“Sina Treaty” is one of the short stories from the collection of “Hey Hey Language” written by Egyptian author Yusuf Idris (1991-1991). The present research has tried to examine outstanding narrative elements of the mentioned story with a descriptive-analytic approach in order to illustrate the issue of resistance and confidence in it. The results indicate that this short story, unlike many other author’s stories the persona is often introduced by direct and indirect characterization and these characters are the symbol of the mood and the morale of their nations and their governments. The main theme of the story refers to the confrontation of the great powers over domination of the weak countries from various aspects of political, social, economic, and... and the message of the story is the call for self-sufficiency, self-confidence and resistance.